A Survey of the views of college students on academic dishonesty - Kasayira, Joseph M.; Musingarabwi, S.; Nyanhongo, S.; Chipandambira, K.S.; Sodi, T. (Routledge, 2021)
The purpose of the study was to examine students' views on dishonest academic behaviours. First year students from Mkoba Teachers' College in Zimbabwe's city of Gweru (n = 152) responded to an open-ended questionnaire that was used to collect data. Knowing examination questions or assignment answers in advance was rated as the worst dishonest academic behaviour engaged in at the college. Lack of preparation was put forward as the main reason why some students engage in academic cheating. Popular proposals for dealing with academic dishonesty included; encouraging students and lecturers to maintain their integrity, severely punishing perpetrators and enforcing security of examination materials. The findings have implications on how responsible authorities communicate appropriate norms to students.